Effect of annealing on mechanical and morphological properties of Poly(L-lactic acid)/Hydroxyapatite composite as material for 3D printing of bone tissue growth stimulating implants; IOP Conference Series: Materials Science and Engineering; Vol. 511 : Perspective Materials of Constructional and Medical Purpose - Dubinenko G. E. Gleb Evgenjevich; Zinovyev (Zinovjev, Zinoviev) A. L. Alexey Leonidovich; Bolbasov E. N. Evgeny Nikolaevich; Novikov V. T. Viktor Timofeevich; Tverdokhlebov S. I. Sergei Ivanovich (2019, 2019)
Title screen